Immunohistochemical Evaluation and Clinicopathological Correlation of Mer and Axl Tyrosine Kinase TAM Receptors in Cutaneous Melanoma - Andrea Pontara; Giovanni Paolino; Vanesa Gregorc; Santo Raffaele Mercuri; Alessandra Bulotta; Pietro Bearzi; Claudio Doglioni; Nathalie Rizzo (Dermatology Practical & Conceptual, 2020)
Background: Malignant melanoma (MM) is potentially the most dangerous form of skin tumor. In the last few years, the so-called TAM receptors, a unique family of tyrosine kinase (TK) receptors, have become increasingly important.